Genetic structure and selection in subdivided populations - Rousset, François, 1967- (Monographs in population biology, 2013)
Various approaches have been developed to evaluate the consequences of spatial structure on evolution in subdivided populations. This book is both a review and new synthesis of several of these approaches, based on the theory of spatial genetic structure. François Rousset examines Sewall Wright''s methods of analysis based on F-statistics, effective size, and diffusion approximation; coalescent arguments; William Hamilton''s inclusive fitness theory; and approaches rooted in game theory and adaptive dynamics. Setting these in a framework that reveals their common features, he demonstrates how.